2017
DOI: 10.1139/cjpp-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in patients with heart failure: the value of considering both global longitudinal left ventricular strain and mechanical dispersion

Abstract: In previous studies, mechanical dispersion (MD) predicted ventricular arrhythmias independently of left ventricular ejection fraction (LVEF). Moreover, the combination of MD and global longitudinal strain (GLS) increased the prediction of arrhythmic events. We investigated the prognostic value of a new 2-dimensional strain index, GLS/MD, in patients with heart failure (HF). We analyzed 340 consecutive HF outpatients in sinus rhythm. Echocardiography was performed at 1.6 ± 0.4 months after hospital discharge. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
5
0
5
Order By: Relevance
“…Blood pressure control remains an element of utmost importance in patients with cardiovascular diseases and one of the first actions to be considered for patients already diagnosed with coronary artery disease or with heart failure [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure control remains an element of utmost importance in patients with cardiovascular diseases and one of the first actions to be considered for patients already diagnosed with coronary artery disease or with heart failure [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that (1) PSD is a more sensitive and accurate indicator than GLS in the detection of early LV systolic dysfunction. PSD estimates whether the peak time of long axis strain of the LV myocardium is consistent [10][11][12] . Recent paper has also shown that PSD is associated with an elevated risk of fatal arrhythmias and sudden cardiac death in patients with coronary artery disease and hypertension 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The emerging study of peak strain dispersion (PSD) identifies whether the peak time of long axis strain of LV myocardium is consistent, which can directly reflect the effective work of the heart and make up for the deficiency of GLS in evaluating LV systolic function [10][11][12] . PSD is used to evaluate the early systolic dysfunction of LV by combining the coordination and synchronization of cardiac mechanical movement, and this index has been applied to assess early LV systolic dysfunction in some diseases, such as mitral valve prolapse 13 , aortic stenosis 14…”
Section: Value Of Peak Strain Dispersion In Discovering Left Ventricumentioning
confidence: 99%
“…Основными конечными точками в исследованиях, где проводилась оценка ГПД и/или МД ЛЖ, являлись "аритмическая" конечная точка (5 исследований) [14,18,19,21,25], большие сердечно-сосудистые неблагоприятные события (MACE -Major adverse cardiovascular events) (5 исследований) [15,16,20,22,24] и обратное ремоделирование ЛЖ (1 исследование) [23].…”
Section: конечные точки и неблагоприятные исходыunclassified
“…Совокупность указанных событий мы рассчитывали, как большие MACE, с целью проведения дальнейшего метаанализа. В большинстве исследований, включенных в наш анализ, были представлены данные ГПД ЛЖ [14][15][16][17][19][20][21][22][23][24][25], в трех исследованиях [14,16,21], кроме того, представлены показатели МД ЛЖ, и в одном исследовании [18] проводилась только оценка значений МД ЛЖ. В таблице 3 представлены основные значения показателей ГПД и МД ЛЖ, а также данные о конечных точках и количестве событий в каждой группе.…”
Section: конечные точки и неблагоприятные исходыunclassified